IDENTIFIKASI CACAT BOTOL AIR MINUM 600 ML DENGAN PENDEKATAN SIX SIGMA - Virman Abdillah, Virman Abdillah; Wahid, Abdul (Metode : Jurnal Teknik Industri, 2024)
Many people choose bottled drinking water because it has been processed and meets drinking water quality standards so it is safe for consumption. Based on data from the Indonesian Bottled Drinking Water Companies Association, in 2014, Indonesians consumed 23.1 billion liters of bottled drinking water, an increase of 11.3 percent compared to 2013 which was only 20.48 billion liters One of the reasons the product does not sell in the market is the weakness of production management, especially the lack of precision in the production process. Constraints that can cause defects in the blowing process include mismatched air pressure or oven settings, which can result in defects such as unmelted bottoms, tilted bottle necks, white bottoms, torn or burst bottles, or bottle shapes that are not as expected. PT. TBK is one of the companies that produces bottled drinking water in 600 ml bottles. Efforts that can be made by the company are to improve product quality through quality control. Six Sigma is a method used for continuous process improvement and enhancement. Research at PT. TBK aims to identify the main factors of product failure during production and analyze the sigma level of 600 ml bottle defects. From the results of the DPMO calculation converted to the Sigma value, a value of 0.79 was obtained with an average DPMO of 1337.39. This means that the 600 ml bottle blowing process produced is above average or has reached the standard.